A coexistence of multi-relaxor states in 0.5BiFeO3–0.5BaTiO3. Issue 18 (15th December 2017) - Wei, Yongxing; Jin, Changqing; Zeng, Yiming; Wang, Xiaotao; Gao, Dong; Wang, Xiaoli
Abstract: Here we report our investigations on a pseudo-cubic 0.5BiFeO3 –0.5BaTiO3 ceramic (0.5BF–0.5BT) in which ferroelectric relaxor and antiferromagnetic and magnetic relaxor orders coexist. The temperature dependence of ferroelectric hysteresis loops and dielectric data confirms the existence of the ferroelectric relaxor state. The temperature of the maximum dielectric constant (Tm ) at 1 MHz and electric freezing temperature (Tf ) are 584 K and ~250 K, respectively. The magnetic data imply that a Neel transition occurs below 174 K. Most importantly, a magnetic relaxor order appears below ~6 K. The magnetic states of 0.5BF–0.5BT are rather different from those of BF–BT ceramics with the low BT concentration.